Profitability analysis of paddy production: A case of agricultural zone 1, Niger State Nigeria (Journal of the Bangladesh Agricultural University, 2018)
This study estimated the profitability of rice production among small scale farmers in Bida agricultural zone of Niger state. The study utilized a multi-stage random sampling technique to select a total of one hundred and five (105) rice farmers in the area. The data was collected through a well-structured questionnaire from four communities in the study area. Descriptive statistics and farm budgeting tools were used for the analyses. The descriptive analysis showed that the farmers are highly productive between the age range of 37- 48 years. Furthermore, results also revealed land area cultivated by the farmers to be generally below two hectares. The finding further revealed the variable cost per hectare for rice production to be $126,100 per production cycle, while total revenue of $227,500 was realized by the respondents. The results also revealed cost of labour to account for the largest portion (54.0%) of the total variable cost. This is followed by the cost of seed, fertilizer, transportation, herbicide, pesticide and bagging. The farm budgeting analysis revealed the costs and returns of rice production to be profitable with a gross margin of $101,400 and net farm profit of $98,546.4. The gross profit ratio was calculated to be 0.45 which implies that farmers are selling their rice produce at a relatively high profit percentage. Based on the results obtained from the study, it was concluded that rice production in Bida Agricultural Zone of Niger State is profitable. Hence, the cultivation of rice is an important enterprise that should be encourage, considering the fact that it is a major staple. It is therefore recommended that timely availability of farm inputs such as improved seed variety and agrochemicals will further boos trice production in the area. Furthermore, provision of credit facilities to small scale farmers is a viable policy to be pursuedJ. Bangladesh Agril. Univ. 16(1): 88-92, April 2018